On the Manifolds of Eigenvectors of Linear and Quasilinear Finite-Dimensional Self-Adjoint Operators. II - Dymarskii, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate the manifold of normalized eigenvectors of self-adjoint operators. We present the homotopic classification of typical quasilinear eigenvector problems based on the properties of this manifold.